Examining reasons for post-purchase satisfaction in buying local brands: When local meets local - Md Isa, Azwardi; Saud, Mohammad Basir; Ismail, Md Daud (Elsevier Taiwan LLC, 2015)
This paper relies on social identity theory to explore post-purchase satisfaction for buying local brands. Concepts including ethnocentrism, self-congruity, corporate brand, service quality and product characteristics are applied towards the customers of Proton and Perodua, two of Malaysia's national automobile brands. The primary purpose is to examine in what ways Proton customers differ from Perodua customers. Using a survey method, 478 respondents were recruited for Proton and 235 for Perodua. The study was carried out at service centres for both brands. Three important findings are reported in this study: first, domestic purchasing is not necessarily related to ethnocentrism; second, consumers are rational; and third, measurement equivalence analysis is important if a study has different types of respondents. These findings are in opposition to other consumer studies that have highlighted ethnocentrism as the primary reason for buying local brands, and this study suggests that there is more to consumer choice than ethnocentric considerations.